2000
DOI: 10.1067/mcp.2000.108196
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced effect of caprylocaproyl macrogolglycerides on nasal absorption of IS-159, a peptide serotonin 1B/1D-receptor agonist

Abstract: 2% caprylocaproyl macrogolglyceride markedly increased the absorption of IS-159 through the nasal mucosa and elicited only mild irritant effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…In the presence of CCM, the absorption of 15-159 was fast, as evidenced by a median t max that ranged between 10 and 20 min for the different dose groups. This finding is in agreement with a previous study in which a value of 15 min was reported [13] and is consistent with absorption through the nasal mucosa [17]. The pharmacokinetics of alnitidan [18], an investigational5-HT 1BIl D receptor agonist, and sumatriptan [19,20] were also investigated after intranasal administration.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In the presence of CCM, the absorption of 15-159 was fast, as evidenced by a median t max that ranged between 10 and 20 min for the different dose groups. This finding is in agreement with a previous study in which a value of 15 min was reported [13] and is consistent with absorption through the nasal mucosa [17]. The pharmacokinetics of alnitidan [18], an investigational5-HT 1BIl D receptor agonist, and sumatriptan [19,20] were also investigated after intranasal administration.…”
Section: Discussionsupporting
confidence: 81%
“…There was a tendency towards a higher frequency of these adverse events in the 4 and 6 mg dose groups. These results confirm those obtained in a previous study [13].…”
Section: Tolerabilitysupporting
confidence: 83%
See 1 more Smart Citation
“…A score of 10 was considered the least tolerable. This scale is analogous to Visual Analog Scales and has been adapted from a previous study evaluating the tolerability of a nasal formulation (11). Subjects also completed a pain and subjective discomfort questionnaire for the i.n.…”
Section: Methodsmentioning
confidence: 99%
“…Enhanced absorption might be achieved using positively charged liposomes, which confer a bioadhesive effect on the negatively charged nasal mucosa [102]. Furthermore, intranasal peptide delivery might be markedly increased by caprylocaproyl macrogolgycerides by enhancing absorption through the nasal mucosa [103].…”
Section: Intranasal Drug Deliverymentioning
confidence: 99%